PENGARUH PREHEAT TERHADAP STRUKTUR MIKRO, SIFAT MEKANIS DAN KETAHANAN KOROSI PADA SAMBUNGAN LAS TAK SEJENIS ANTARA BAJA TAHAN KARAT AUSTENITIK AISI 304 DAN BAJA KARBON RENDAH A 36 - , SAIFUDIN; , Mochammad Noer Ilman, S.T., M.Sc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Welding of dissimilar metals between stainless steel and carbon steel is widely used in a number of engineering practice, including railways, automotive, ship and other industries. However, one of the problems of welding austenitic stainless steel is precipitation of chromium carbide (Cr3C2) or Cr23C6 which nucleates at austenite grain boundaries. This precipitation occurs due slow cooling from the temperature of 900oC to 450oC. On the other hand, low carbon steel has excessive hardening in the HAZ if the cooling rate is high, causing a decrease in toughness. One of the solution is introducing preheating, so that the cooling rate becomes slow and reduces temperature gradient between weld metal and the base plate. The purpose of this study is to improve the mechanical properties especially toughness of weld joint using preheat. AISI 304 stainless steel plates were welded with A 36 carbon steel plates using MIG with a filler of ER 308. Welding was carried out using voltage of 20 Volt, current of 100 Ampere and heat input of 1 kJ / mm. Preheat temperature of 100oC, 200oC and 300oC. Tests include the nature of microhardness, microstructure, tensile test, impact test and corrosion resistance. The results show that hardness values vary depending on welding metallurgy, center of welding, HAZ and base metal. Preheat reduce weld hardness and increas ductility, toughness and corrosion resistance of welding.